Characteristics of shock attenuation during fatigued running - Mercer, J. A.; Bates, B. T.; Dufek, J. S.; Hreljac, A. (Journal of Sports Sciences, 2003)
The aim of this study was to examine shock attenuation before and after completing a maximal effort graded exercise test while running on a treadmill. Ten individuals ran before and after a maximal graded exercise test with running speed controlled between conditions. Transfer functions were calculated using surface-mounted accelerometers to represent shock attenuation. An accelerometer was mounted on the distal aspect of the tibia and another on the anterior aspect of the forehead. Ten strides were analysed in each condition for all participants. Paired t-tests were used to compare each dependent variable (shock attenuation, stride length, rate of oxygen consumption) between conditions (running before vs after the exercise test). Oxygen consumption was 16% greater when running after the graded exercise test (47.9 +/- 5.0 ml x kg(-1) x min(-1); mean+/-s) than when running before it (41.1 +/- 2.7 ml x kg(-1) x min(-1)) (P < 0.05). Stride length was similar during running before (2.71 +/- 0.15 m) and after (2.75 +/- 0.17 m) the graded exercise test (P > 0.05). Shock attenuation was, on average, 12% lower during running after (-9.8 +/- 2.6 dB) than before (-11.3 +/- 2.7 dB) the graded exercise test (P < 0.05). We conclude that less shock was attenuated during fatigued than non-fatigued running and that only subtle changes in stride length were made while fatigued.